9‐epi‐Artemisinin – How a Single Stereo Center Affects Chemical Reactivity under Reductive Conditions. Issue 5 (4th May 2022) - Kweku Anokwah, Daniel; Furet, Pascal; Denay, Regis; Kotoni, Dorina; Bixel, Dominique; Allmendinger, Thomas
Abstract: 9‐ epi ‐Artemisinin occurs as a minor by‐product when artemisinin is obtained from natural or semi‐synthetic sources. The preparation of β‐artemether from artemisinin by reduction with sodium borohydride proceeds normally even when the 9‐epimer is present. However, the 9‐epimer undergoes rearrangement to peroxy acetals. The results are ascribed to the different stabilities of the corresponding dihydro‐intermediates due to steric hindrance as suggested by quantum mechanical calculations. Abstract :